2018
DOI: 10.1038/s41598-018-22640-y
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin generates oxidative stress which is accompanied by rapid shifts in central carbon metabolism

Abstract: Cisplatin is commonly utilized in the treatment of solid tumors. Its mechanism of action is complex and multiple mechanisms of resistance have been described. We sought to determine the impact of cisplatin-generated oxidative stress on head and neck squamous cell carcinoma (HNSCC) proliferation, survival and metabolic activity in order to identify a potential metabolic signature associated with cisplatin response. DNA-bound cisplatin represents a small fraction of total intra-cellular cisplatin but generates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 49 publications
(38 reference statements)
6
63
1
1
Order By: Relevance
“…A study by Yu et al suggests that glycolysis, more specifically the conversion of pyruvate into lactate, which requires NADH, is the predominant metabolic pathway to be affected by cisplatin as a result of oxidative stress. In addition to biochemical assays in cultured cells, the authors showed that the exposure of tumor xenografts to a single dose of cisplatin resulted in a rapid decrease in tumor lactate levels, and that this correlated with effects on the delay of tumor growth (20). By measuring glucose uptake, lactate production and the expression of glycolysis-related proteins, Wang et al found that the glycolysis levels of breast and cervical cancer cells were reduced after cisplatin treatment, resulting in the inhibition of cell growth and proliferation (21).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yu et al suggests that glycolysis, more specifically the conversion of pyruvate into lactate, which requires NADH, is the predominant metabolic pathway to be affected by cisplatin as a result of oxidative stress. In addition to biochemical assays in cultured cells, the authors showed that the exposure of tumor xenografts to a single dose of cisplatin resulted in a rapid decrease in tumor lactate levels, and that this correlated with effects on the delay of tumor growth (20). By measuring glucose uptake, lactate production and the expression of glycolysis-related proteins, Wang et al found that the glycolysis levels of breast and cervical cancer cells were reduced after cisplatin treatment, resulting in the inhibition of cell growth and proliferation (21).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Yu et al showed that only a small fraction of cisplatin (<10%) bound to the DNA will generate a significant increase in Îł-H2AX foci formation [61]. This group also found that the main mechanism for these effects is the induction of oxidative stress, as observed by the ability of the free radical scavenger N-acetyl cysteine (a precursor of glutathione) to reverse cisplatin toxicity and Îł-H2AX foci formation [61].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Yu et al showed that only a small fraction of cisplatin (<10%) bound to the DNA will generate a significant increase in Îł-H2AX foci formation [61]. This group also found that the main mechanism for these effects is the induction of oxidative stress, as observed by the ability of the free radical scavenger N-acetyl cysteine (a precursor of glutathione) to reverse cisplatin toxicity and Îł-H2AX foci formation [61]. In addition, a recent study performed on non-tumorigenic, immortalized ovarian surface epithelial cells reported that 10 ”M NE reduced the levels of DNA damage in the presence of ROS-generating molecules (i.e., bleomycin) [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, they are more flexible in terms of setup and can be used to image therapy effects noninvasively as often as clinically necessary after initial and subsequent radiotherapy sessions . Chemotherapy, photodynamic therapy, or other treatments can be equally followed . Molecular monitoring of radiation effects by MR allows for translation of laboratory research to the clinic, as parallel in‐cell , ex vivo (on biological samples stemming from patients) and in vivo imaging of the effects of radiation can be conducted with the same approach.…”
Section: Introductionmentioning
confidence: 99%
“…19 Chemotherapy, photodynamic therapy, or other treatments can be equally followed. 11,[20][21][22] Molecular monitoring of radiation effects by MR allows for translation of laboratory research to the clinic, as parallel in-cell, ex vivo (on biological samples stemming from patients) and in vivo imaging of the effects of radiation can be conducted with the same approach.…”
Section: Introductionmentioning
confidence: 99%